Uji Efektivitas Berbagai Dosis Serbuk Biji Pinang Sebagai Moluskisida Nabati Terhadap Mortalitas Keong Mas Pada Tanaman Padi - Agustian, Hilmi Fadhil; Rizali, Akhmad; Nugraha, Muhammad Imam (Agroekotek View, 2023)
Rice production (Oryza sativa L.) in Indonesia decreased in 2019, one of the causes was pest attacks. The golden snail (Pomacea canaliculata L.) is one of the potential pests because the heaviest attack can cause a decrease in rice production. Therefore it is necessary to take control measures to suppress the pest population, one way that can be used is with vegetable pesticides made from betel nut seeds because the content in it can cause toxic effects. This study aims to determine the effectiveness and also the best dose of the application of areca nut powder on the mortality of golden snails. This research was conducted in May 2021 – July 2021, at the Agroecotechnology Greenhouse, and on Jalan Qiramah Alam house number 13 B, Landasan Ulin District, Banjarbaru. The method used was a one-factor Completely Randomized Design (CRD) with treatment P0 (control), P1 (dose of 1 g), P2 (dose of 2.5 g), P3 (dose of 5 g), P4 (dose of 7.5 g), and P5 (dose of 10 g) and each treatment was repeated 4 times. The results obtained showed that the application of areca nut powder was effective in controlling golden snails in the P3 treatment with a dose of 5 g was able to provide the best results on all parameters, as well as the right dose in controlling 50% of the population, with a dose of 2,343 g areca nut powder.